Strategic Model in the Development of Economic Transformation in Gorontalo City - Dian Rahayu Maku; Mohammad Zubair Hippy; Siti Rahmatia Machieu; Mustakim Mokoginta; Djunaida Kandow; Meilan Daud; Indriyati Lanangawa (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to formulate a model for the development of economic transformation in Gorontalo City. The research approach used is mixed method explanatory design, which combines quantitative and qualitative analysis. Data was collected through questionnaires, observations, documentation, and Focus Group Discussions (FGD) with 10 experts consisting of OPDs, communities, and related stakeholders. Quantitative data analysis used the Analytical Hierarchy Process (AHP) method and the qualitative Miles and Huberman model. The results of the study show that local governments are the main actors in the development of a smart economy, supported by universities, investors, and research institutions. The dominant factors that affect economic transformation in Gorontalo City are human resource capacity and digital literacy, entrepreneurial ecosystem, and circular economy innovation. The key strategies identified include community empowerment, entrepreneurship digitalization, strengthening innovation centers, and developing digital infrastructure. Gorontalo City still faces challenges such as low digital literacy, uneven infrastructure, and limited access to technology, but multi-sector collaboration and exploration of creative economy potential have opened up opportunities for innovation-based economic growth. The priority strategies in the development of economic transformation in Gorontalo City are community empowerment and business model development to create jobs, digitalization of circular economy-based entrepreneurship and financial inclusion and optimization of smart economic innovation centers based on education, research, and technology. In conclusion, the progressive economic model implemented is able to encourage sustainable achievement through innovation, cross-sector collaboration, and policies that support digital transformation. Therefore, it is necessary to accelerate the equitable distribution of digital infrastructure, increase human resource capacity, and strengthen policies and collaboration to realize an inclusive and sustainable economic ecosystem in Gorontalo City, especially in optimizing the efforts of Gorontalo City as a City of Services.